LaPO4 coating on alumina-based fiber: Strength retention of fiber and improvement of interfacial performances. Issue 6 (15th March 2022) - Xu, Zhongkai; Zhang, Jian; Chen, Zhe; Sun, Xiaohong; Lv, Xuming; Guo, Ruisong; Cui, Fengdan; Xiong, Kunzhou; Gong, Zhiyou; Yuan, Zhuang; Zheng, Chunming
Abstract: The characteristics of the interface are the key factors that determine the mechanical properties and fracture behavior of fiber-reinforced ceramic matrix composites. Design and preparation of coatings which can preserve fiber strength and maintain appropriate interfacial bonding strength are of great challenges. LaPO4 coating is a promising weak interface coating for oxide fiber reinforced oxide ceramic matrix composites. Through this coating, the toughening mechanism of the composite such as fiber pulling out and fiber debonding is triggered. The LaPO4 coating was deposited on the surface of alumina-based fibers by a solution precursor heterogeneous precipitation method. The effects of different precursors and different deposition temperatures on fiber strength were studied, and the mechanism of the strength degradation of the coated fiber was analyzed. It was found that the fibers coated with phytic acid precursor and deposited at 90 °C had the highest tensile strength compared to other coated fibers. The retention of strength is attributed to its loosely stacked coating. Besides, a single fiber pullout test was carried out to evaluate the effect of the coating on the interface of the composites. The results show that the composites coated by depositing citric acid precursor and phytic acid precursor at 90 °C can reduce the interfacial bonding strength by 32.5% and 46.7%, respectively compared to uncoated composites. This study has potential application value in the preparation of ceramic matrix composites used in oxidation and high temperature environments.